Servant Leadership, Social Work Environment, and Turnover Intention in Microfinance: The Mediating Role of Job Satisfaction - Ilmiah, Indah; Mildawani, Tri Susetyaning (PT FORMOSA CENDEKIA GLOBAL, 2024)
In a growing company, various issues inevitably arise. These issues can disrupt and hinder ongoing business processes. One of the human resource (HR) problems is the increasing intention of employees to leave the company. Therefore, turnover intention in the company needs to be examined further. This study analyzes turnover intention regarding servant leadership style and social work environment with job satisfaction as a mediator. This research is a type of quantitative study conducted at PT PNM Mekaar Region Surabaya 1. The data collection method used in this study is a questionnaire. The sampling technique employed is non-probability sampling. This study's population comprises PT PNM Mekaar Region Surabaya 1 employees. The analysis method used in this study is Structural Equation Modeling (SEM) with SmartPLS software. The results indicate that the servant leadership style affects job satisfaction, and the social work environment also affects job satisfaction. Moreover, the servant leadership style influences turnover intention. However, the social work environment does not affect turnover intention, and job satisfaction moderately influences turnover intention.